Rules of engagement: The role of mistreatment from patients in the nurse, physician and advanced practice provider experience - Katherine Meese; Alejandra Colón-López; Aoyjai Montgomery; Laurence Boitet; David Rogers; Patricia Patrician (The Beryl Institute, 2022)
The objective of this study is to examine the incidence of reported stress due to mistreatment by patients toward clinicians and the role of mistreatment from patients along with organizational factors in clinician distress. A survey of clinicians was conducted at a large academic medical center, resulting in a final analytic sample of 1,682 physicians, nurses, advanced practice providers and clinical support staff. Nurses reported the greatest incidence of mistreatment by patients as a major stressor (18.69%), followed by Advanced Practice Providers (11.26%), Clinical Support Staff (10.36%), and Physicians (7.69%). Logistic regression analysis was conducted to determine the relationship of individual- and organization-level characteristics with the odds of reporting mistreatment from patients as a major stressor. Overall findings indicate that nurses and those who work in the ER and ambulatory or outpatient clinics were more likely to be stressed from mistreatment by patients than other clinicians. Stress due to mistreatment by patients was also associated with higher Well-Being Index (WBI) distress scores, rapid changes in workflows or policies, ongoing care of COVID-19 patients, under-staffing, and low perceived organizational support. Gender or sexual minorities (not identifying as male or female) and younger (18-34 years of age) healthcare workers were also more likely to experience stress from mistreatment by patients. Individual resilience was not statistically significantly associated with reported stress from mistreatment by patients. Organizations must examine expectations for patient and visitor behavior in tandem with service standards for clinicians toward patients. Experience Framework This article is associated with the Staff & Provider Engagement lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Staff%20%26%20Provider%20Engagement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.